Mechanical, Elastic and Thermal Properties of Hexagonal BC2N Superhard Material - Chaurasiya, N.; Rai, S.; Yadawa, P. K. (Journal of Scientific Research, 2022)
The ultrasonic properties of the hexagonal BC2N superhard material were studied at temperature-dependent following the interaction potential model. Higher-order elastic constants are used for the determination of other ultrasonic parameters. The temperature variation of the ultrasonic velocities is evaluated along with different angles with z-axis (unique axis) of the crystal using the second-order elastic constants temperature variation of the thermal relaxation time, and Debye average velocities are also calculated along with the same orientation. The temperature dependency of the acoustic properties is discussed in correlation with elastic, thermal, and mechanical properties. It has been found that thermal conductivity and thermal energy density are the main contributors to the behavior of ultrasonic attenuation as a function of temperature. The responsible cause of attenuation is phonon-phonon interaction. Mechanical properties of BC2N superhard material at temperature 400K are better than at other temperatures because, at this temperature, it has low ultrasonic attenuation. Superhard material BC2N has many industrial and engineering applications.